Gender roles and greenhouse gas emissions in intensified agricultural systems in the mid-hills of Nepal - Raut, N; Raya, B; Sitaula, BK; Bajracharya R M; Kristjanson, Patricia M. (2013)
This paper assessed gender differences in agricultural activities that have a potential effect on N2O emissions from agricultural soils in the Ansikhola watershed of the mid-hill region of Nepal. Multiple methods were used to collect data, including a questionnaire survey (310 households), six focus group discussions, five key informant interviews and field gas flux measurements over a year. Results indicate that women are involved in farmyard manure (FYM) collection, transport and application. Decisions regarding which crops to plant and about purchases of chemical fertilizers have changed over the last 20 years, with women now being more included in such decisions, although this is happening more among higher and middle caste groups than in the lower castes. Involvement of women in community-based agriculture-related institutions has also increased, regardless of caste. Field flux measurements show variation in N2O emissions depending on the type of land use (e.g. Khet versus Bari), cropping system (traditional versus intensified) and across seasons (e.g. higher during the rainy season). The results show that increased fertilizer applications over 20 years has resulted in higher intrinsic propensity of the soil to emit N2O. Therefore the ongoing intensification of agriculture in South Asia may result in increasing N2O emissions.